Perancangan dan Pengembangan Video Company Profile PT. Dua Utama Jaya - Tony Wibowo; Maya Melenia Febriany (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
PT. Dua Utama Jaya is a company that engaged in training and certification and located in Batam City. This company has been established since 2004 and focuses on providing internationally certified training to support industry, construction, oil, And gas. The problem experienced by the company is the lack of information about services and only through brochures, websites, and through individuals. Therefore, the company requires media information about the Company Profile to inform the public in introducing the company. The methodology applied in this research is the Applied research. To produce a good and quality company profile video-based media design, it is used for supporting applications such as Adobe Premiere CS6 and Filmora. The results of the Video Company Profile will be uploaded to the Youtube Platform owned by PT. Two Utama Jaya. Provide Information about The Company to The Public and Improve The Image for The Company